2006
DOI: 10.1016/j.clpt.2005.12.302
|View full text |Cite|
|
Sign up to set email alerts
|

Severe arrhythmia as a result of the interaction of cetirizine and pilsicainide in a patient with renal insufficiency: First case presentation showing competition for excretion via renal multidrug resistance protein 1 and organic cation transporter 2

Abstract: A 72-year-old woman with renal insufficiency who was taking oral pilsicainide (150 mg/d) complained of feeling faint 3 days after she was prescribed oral cetirizine (20 mg/d). She was found to have a wide QRS wave with bradycardia. Her symptoms were relieved by termination of pilsicainide. The plasma concentrations of both drugs were significantly increased during the coadministration, and the cetirizine concentration decreased on cessation of pilsicainide despite the fact that treatment with cetirizine was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 21 publications
(66 reference statements)
0
26
0
6
Order By: Relevance
“…The mechanism of the reported renal interaction of the combination of cetirizine and pilsicainide in an elderly woman with renal insufficiency was claimed to be due to an interaction with P-gp and OCT2, as proposed by Tsuruoka et al (2006); however, in vitro studies with the human transport proteins have failed to show inhibitory properties for cetirizine or its enantiomers at therapeutic concentations. Indeed, several studies suggest different elimination mechanisms for pilsicainide and cetirizine .…”
Section: Transporter-based Interactions Involving Drugs Used To Treatmentioning
confidence: 93%
“…The mechanism of the reported renal interaction of the combination of cetirizine and pilsicainide in an elderly woman with renal insufficiency was claimed to be due to an interaction with P-gp and OCT2, as proposed by Tsuruoka et al (2006); however, in vitro studies with the human transport proteins have failed to show inhibitory properties for cetirizine or its enantiomers at therapeutic concentations. Indeed, several studies suggest different elimination mechanisms for pilsicainide and cetirizine .…”
Section: Transporter-based Interactions Involving Drugs Used To Treatmentioning
confidence: 93%
“…We previously reported that PLC is excreted via the organic cationic transport system in the renal proximal tubule in humans [8] and the elimination of PLC was not inhibited by verapamil, a potent P-glycoprotein inhibitor, in human and experimental studies [9]. In contrast, Tsuruoka et al [10] suggested that the excretion of PLC in the kidney is mediated by human multidrug resistance protein 1 based on the results of a pharmacokinetic drug-drug interaction study of PLC. Moreover, a case report suggested that the metabolic rate of PLC was increased by cytochrome p450 induction [11].…”
Section: Introductionmentioning
confidence: 92%
“…1, and ions at 273 → 110 and 325 → 79, respectively, were selected for subsequent quantitative analysis. The calibration curve for PLC ranged from 5 to 2000 ng/mL in human plasma, from 5 to 500 ng/mL in ultrafiltered plasma solution, and from 25 to 2000 ng/mL in urine, which were the concentration ranges of PLC in biological fluids in previous reports [7][8][9][10]. In addition, a LLOQ was obtained by simple extraction procedure using diethylether.…”
Section: Chromatographic Optimizationmentioning
confidence: 99%
“…Il est aussi difficile pour un praticien de suspecter et/ou de repé rer dans un article les limites du plan expé rimental, des erreurs de calcul et d'unité s et des dé saccords avec les ré sultats d'autres travaux, l'ensemble pouvant remettre en cause les conclusions du travail pré senté . C'est le cas de l'é tude rapportant une arythmie sé vè re due à l'interaction entre le pilsicainide et la cetirizine[54,55]. libellé officiel qui donne parfois un faible é clairage sur les risques encourus Au niveau de l'Afssaps, la mé thodologie qui guide l'inté gration et la non-inté gration des interactions dans le thé saurus est dé crite et accessible sur le site Internet de cet organisme.…”
unclassified